2017
DOI: 10.1016/j.jtemb.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluoride on insulin signaling and bone metabolism in ovariectomized rats

Abstract: Fluoride is an essential trace element for the maintenance of bone health owing to its capacity to stimulate proliferation and osteoblastic activity that can lead to increased bone formation. However, excessive sodium fluoride (NaF) intake can impair carbohydrate metabolism thereby promoting hyperglycemia, insulin resistance, and changes in insulin signaling. Thus, this study aimed to evaluate the effect of chronic treatment with NaF in bone metabolism, insulin signaling, and plasma concentrations of glucose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Fluoride can be consumed from soil, water, and vegetation. Skeletal and dental Fluorosis, stiffness of the joints and emaciation usually result from chronic fluoride toxicity [3] , [4] , [5] , [6] . Like other Hemotoxic agents fluoride also shows deleterious effects on reproductive capacity of animals and their milk production [7] , [8] , [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Fluoride can be consumed from soil, water, and vegetation. Skeletal and dental Fluorosis, stiffness of the joints and emaciation usually result from chronic fluoride toxicity [3] , [4] , [5] , [6] . Like other Hemotoxic agents fluoride also shows deleterious effects on reproductive capacity of animals and their milk production [7] , [8] , [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…A significant effect of F on OC expression has been found to occur in adults at serum F levels of 1.0 μM [154] or when urinary F levels exceed 0.62 mg/L in adolescent children [155]. Consistent with this data, several in-vivo studies have reported that chronic F exposure enhances plasma insulin levels and promotes insulin resistance in rodents [211,212,213,214,215]. A similar association has also been found in humans chronically exposed to F [216].…”
Section: Molecular Mechanisms Of Fluoride Inhibition Of Iodine Hommentioning
confidence: 72%
“…This might have resulted from the quite distinct fluoride content of the mineral-rich waters (being the main difference between these 2 waters: lower in Pérez-Granados et al [58]) and the low-sodium diet of the Schoppen et al volunteers [61]. Nevertheless, it should pointed out that fluoride modulation of insulin secretion, action and clearance is still not completely clarified [75,146]. In contrast, NaCl restriction has been revealed to deteriorate glucose tolerance and high NaCl intake to regulate glucose homeostasis (the latter through adiponectin production) [147,148,149,150].…”
Section: Discussionmentioning
confidence: 99%